Effect of different Concentrations of Cadmium Nanoparticle, PH and Salinity on Production of Astaxanthin in Haematococcus Pluvialis - Hong, Yee Zhen (2016)
Haematococcus pluvialis is one of the potent microalgae for the production of secondary carotenoid, astaxanthin. Astaxanthin has great commercial value due to its high antioxidant properties. However, the mass production of astaxanthin is hindered by the low yield of astaxanthin obtained from the H. pluvialis. Various report have been used heavy metal to induce accumulation of astaxanthin in H. pluvialis, however, using nanoparticle to induce the production of astaxanthin in the same algae so far have not been investigated. In this present study, the objective was investigate the effect of Cadmium pH and salinity. Haematococcus pluvialis was cultured at different pH and salinity in order to find the optimized growth parameter for the growth of H. pluvialis and maximal astaxanthin production. Highest (p<0.05) of growth and astaxanthin production in the algae were found at pH 7 and 0.25% of salinity. The experiment was taken a step further by testing the algae at different concentration of Cd nanoparticle under the optimal growth condition which have been determined previously. Highest (p<0.05) accumulation of astaxanthin was found when the algae exposed at 10mg/mL of Cd nanoparticle. There were no correlation about the growth and astaxanthin formation. Even the Cd nanoparticle inhibit the growth of the algae, but the Cd nanoparticle still could induce astaxanthin accumulation in H. pluvialis. This is due to the ability of nanoparticle and metal could exerted stress on the algae by generating the reactive oxygen species (ROS), as a protective response against the detrimental effect of ROS, astaxanthin was being synthesized by the algae. Thus, we proposed possible mechanism was shared between Cd nanoparticle and Cd heavy metal in the induction of astaxanthin accumulation.